Analysis of The Resolution of Traffic Accident Cases Involving Electric Bicycles in The Jurisdiction of The Sula Islands Police - Rinaldi Anwar; Chairul Muriman Setyabudi; Arthur Josias Simon Runturambi (Transpublika Publisher, 2026)
Traffic accidents involving electric bicycles in the Sula Islands continue to increase; however, regulatory gaps and low levels of safety awareness make case resolution by the police more complex, requiring adaptive and effective legal strategies that are aligned with local social conditions. This study aims to analyse the application of law, case resolution mechanisms, and factors influencing the handling of traffic accidents involving electric bicycles within the jurisdiction of the Sula Islands Police. The study is grounded in several theoretical and conceptual frameworks, including Progressive Law Theory, Public Policy Theory, Management Theory, Traffic Accident Concept, Electric Bicycle Concept, Restorative Justice Concept, Community Policing Concept, Case Resolution Concept, and Police Science Concept. A qualitative case study method is employed to examine empirical conditions and law enforcement practices. The findings indicate that law enforcement in electric bicycle accident cases is constrained by the absence of regional regulations, leading to reliance on supervision and appeals; case settlement therefore adopts an adaptive, restorative justice-oriented approach focused on victim recovery, accountability, and community involvement; and effectiveness is determined by officer competence, resource availability, and integrated, flexible working methods. Overall, this study underscores the urgency of strengthening local regulatory frameworks and institutional capacity to ensure legal certainty, public safety, and substantive justice in a sustainable manner.